تأثير درجة الحرارة على نفاذية التربة الرملية المحسنة بالشمع المصممة كبطانة أرضية للمطمر - وائل حرفوش; رامي أسطه; ديمه سلامه (Tishreen University, 2018)
Temperatures generated within the waste mass, covers , bottom liners and surrounding subsurface soil is considered as one of the most important factors affecting  the performance of the insulation systems in landfills. This is due to its influence on the physical and mechanical of the material properties used in lining, and particularly on the permeability and its modulus. Research aims to study the effect of variations of temperatures on permeability of sandy soil treated with wax, and determine the optimum ratio for the addition of wax that satisfy the required impermeability in landfills within thermal changes. The importance of the research is to evaluate  the impact of temperature variation on the effective performance of compacted sandy soil treated with wax to be used as a barrier in landfills. Al Bassa landfill in Latakia was  selected as a case study because of its sandy permeable soil and its high water table level where there is a risk of contamination by leakage of leachate into the soil and groundwater. تعتبر درجات الحرارة المتولدة ضمن كتلة النفايات وما يحيط بها من غطاء وبطانة وتربة من أهم العوامل المؤثرة على أداء أنظمة العزل في المطامر. ويرجع السبب في ذلك إلى تأثيرها على الخصائص الفيزيائية         والميكانيكية للمواد المستخدمة في التبطين، وبشكل خاص على النفاذية ومعاملها. يهدف البحث إلى دراسة تأثير درجة الحرارة على نفاذية خلائط التربة الرملية المعالجة بنسب من الشمع، وتحديد النسبة المثلى للشمع التي تحقق النفاذية المطلوبة في البطانة السفلية للمطمر ضمن ظروف التغيرات الحرارية المؤثرة  . تأتي أهمية البحث في تقييم الأثر الحراري على فعالية أداء التربة الرملية المحسنة بالشمع والمرصوصة لاستخدامها كحاجز عزل في المطامر والوصول إلى التصميم المناسب للبطانة السفلية المحقق لدرجة التكتيم المطلوبة مع الظروف الحرارية المحيطة بالبطانة . تم اختيار مطمر البصة في مدينة اللاذقية كتطبيق للدراسة و ذلك بسبب  تربة موقعه الرملية النفوذة ومنسوب المياه الجوفية المرتفع مما يشكل خطر حدوث تلوث في التربة والمياه الجوفية.